Refinement of carbide precipitates in high-Nb TiAl by cyclic aging treatments. (February 2023) - Cao, Jun; Guo, Zhichao; Sun, Tielong; Zhang, Fuqiang; Liang, Yongfeng; Ding, Xianfei; Nan, Hai; Lin, Junpin
Abstract: High-Nb TiAl alloys are considered as new generation of γ -TiAl alloys for applications at higher service temperatures owing to their superior high-temperature oxidation and creep resistance. Addition of C element can further improve its high temperature creep resistance through solid solution strengthening and precipitation strengthening, but the coarse carbide precipitates are not conducive to the mechanical performance improvement. This paper provides a method for refinement of carbide precipitates via solution and cyclic aging treatments in an as-cast Ti-45Al-8Nb-0.9C (at%) alloy. Coarse primary carbides that precipitated during casting were eliminated through solution treatment, while numerous submicron secondary carbides were precipitated through cyclic aging treatments. The crystallographic orientation relationship between the precipitated submicron secondary carbides and the high-Nb TiAl matrix was determined by various transmission electron microscopy characterization methods. This refinement method provides a possible way for refinement of other precipitates in TiAl alloys. Graphical abstract: Image, graphical abstract